2020
DOI: 10.1111/srt.12900
|View full text |Cite
|
Sign up to set email alerts
|

Value of GPSkin for the measurement of skin barrier impairment and for monitoring of rosacea treatment in daily practice

Abstract: Background Stratum corneum hydration (SCH) and transepidermal water loss (TEWL) provide useful information about skin barrier function. This study aimed to determine the value of GPSkin Pro, a new handheld device determining both SCH and TEWL, to measure skin barrier impairment and to monitor barrier function in rosacea in daily practice. Materials and Methods Two pilots were performed. Pilot 1: in 27 healthy participants, GPSkin SCH and TEWL were compared to Aquaflux® and Epsilon® values at the forearm before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…It was weakly correlated with the AquaFlux in one study 45 but correlated well in two other studies. 46,47 Both devices showed greater variation from other devices as higher values of TEWL…”
Section: Gpskinmentioning
confidence: 96%
“…It was weakly correlated with the AquaFlux in one study 45 but correlated well in two other studies. 46,47 Both devices showed greater variation from other devices as higher values of TEWL…”
Section: Gpskinmentioning
confidence: 96%
“…Recent studies have introduced a number of new devices that can measure skin hydration [8][9][10][11] . Grinich et al reported on a novel device for measuring stratum corneum hydration that showed precise and reliable measurements, compared to the currently used devices 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the device has sensors for measuring skin capacitance and can transmit data to a smartphone application, it can analyze skin barrier function at low cost 10 . Logger et al described a novel device for measuring skin hydration that can also be used for clinical purposes 11 . They measured skin hydration in rosacea patients before and after treatment, and found that skin hydration in rosacea patients was impaired before treatment, but restored after treatment 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations